Desvenlafaxine for the Acute Treatment of Depression: A Systematic Review and Meta-analysis - Laoutidis, Z. G.; Kioulos, K. T. (Pharmacopsychiatry, 2015)
Introduction: Desvenlafaxine, the active metabolite of venlafaxine, was approved in 2008 by the FDA for the treatment of depression. The aim of the present review is to provide an overview of the existing trials with desvenlafaxine and assess its overall efficacy and tolerability.Methods: We searched in PubMed, EMBASE and the Cochrane Library for eligible studies (double-blind randomized control trials). A random effects model was used for the estimation of effect sizes.Results: 17 trials were found in total. In the placebo-controlled trials the overall risk ratio for response was 1.24 (1.16–1.32, p<0.001), for remission 1.29 (1.16–1.43, p<0.001), for dropouts 1.16 (0.99–1.35, p=0.066) and for dropouts due to adverse events 1.98 (1.45–2.69, p<0.001). There were no differences between the various doses that were used (i. e., 50 mg, 100 mg, 200 mg, 400 mg). The mean risk ratio for response in the head-to-head trials was 0.90 (0.82–0.98, p=0.014) and for remission 0.82 (0.71–0.95, p=0.009).Discussion: The risk ratios for response and remission were moderate. We further provide some evidence that desvenlafaxine might not be as efficacious as other antidepressants.
Keywords: depression; desvenlafaxine; SNRI; review; meta-analysis